Characterization of Mouse Monoclonal Anti-Glypican-3 Antibody Targeting Liver Cancer - 천유리 (The Graduate School, Ajou University, 2024)
Liver cancer is a leading cause of cancer-related mortality worldwide, necessitating the development of more effective and targeted therapies. Glypican-3 (GPC3), a cell surface proteoglycan overexpressed in liver cancer cells, has emerged as a promising therapeutic target. This study explores the potential of 1B10, a novel Antibody-Drug Conjugates (ADCs) based on a mouse monoclonal anti-GPC3 antibody, designed to target GPC3-expressing liver cancer cells specifically. The binding affinity, stability, and internalization of 1B10 were evaluated through a series of experiments. _x000D_ Firstly, various assays, including ELISA, FACS, and SPR analysis, demonstrated that 1B10 exhibits a high binding affinity for GPC3, with a dissociation constant (KD) of 4.46 × 10-9 M, confirming its specificity and potency. Stability tests indicated that 1B10 maintains its functional integrity and binding affinity after multiple freeze/thaw cycles and remains stable in acidic environments down to pH 6.0, which is characteristic of the tumor microenvironment (TME). These findings underscore the practical applicability of 1B10 under various storage and physiological conditions. _x000D_ Confocal microscopy revealed that 1B10 is efficiently internalized by liver cancer cells, localizing within the cytoplasm and co-localizing with the lysosomal marker LAMP-1 after 2 hours. This internalization is critical for releasing the ADC's cytotoxic payload in proximity to vital cellular machinery, thereby enhancing its therapeutic efficacy._x000D_ The collective data suggest that 1B10 is a promising candidate for targeted therapy in liver cancer. The high specificity, effective internalization, and robust stability of 1B10 highlight its potential to deliver cytotoxic agents directly to cancer cells, paving the way for more effective and less toxic therapeutic options.
학위논문(석사)--약학과,2024. 8
Keywords: Antibody-Drug Conjugate; GPC3; Internalization; Liver cancer; Post-Translational Modifications